Retrofitting of old buildings into museum in Penang : challenges and possible solutions / Syaiful Zahreen Johari Al Hadi and Nurul Huda Muhamad - Johari Al Hadi, Syaiful Zahreen; Muhamad, Nurul Huda (2018)
Heritage buildings are a legacy from the past that needs to be conserved Buildings are to prevent it from being lost forever it is imperative that preservations must be made for the benefit of future generations. However, some of these buildings are at risk from defects and are not being well cared for due to lack of technical knowledge and high cost of repair and maintenance. Hence, retrofitting of a building requires an understanding of the existing building performance before considering the improvement to be made on it. The purpose of this research is to understand the challenges related to retrofitting old Buildings into museums. This study uses a quantitative method which is by distributing questionnaires to the respondents comprising of, the manager, the maintenance staff, the admin and the clerk. One of the highest challenges that respondents gave included strongly on safety aspects of the building structure and for the suitable solution. Respondents commented strongly agree in understanding the terms of retrofitting, implement guidelines and regulations on retrofitting buildings as well as giving more education, training and activities to create awareness.